Ice and ocean processes in the Bellingshausen Sea, Antarctica - Holland, Paul R.; Jenkins, Adrian; Holland, David M. (Journal of Geophysical Research, 2010)
[1] In the vicinity of the Antarctic Peninsula observations show diminishing sea ice and a rapid warming of atmosphere and ocean. These changes have led to the collapse of ice shelves and retreat, acceleration, and thinning of inland ice. However, ocean observations in the center of the nearby Bellingshausen Sea are spatially and temporally coarse. In this study, ocean and sea ice models forced by atmospheric reanalyses are used to investigate this data gap by simulating processes in the Bellingshausen Sea for the years 1979–2007. The model suggests flow features in the region and predicts the basal melting of local ice shelves. Modeled ocean conditions are found to be less variable than in the nearby Amundsen Sea, which is situated closer to foci of annual and interannual atmospheric variability. Melt rates beneath George VI Ice Shelf are investigated in detail, concluding that the ice shelf may have been melting out of balance (and therefore thinning) for decades. The melt rate contains significant interannual variability that the model links to variation in sea ice conditions offshore of the southern end of the ice shelf. This stands in contrast to the Amundsen Sea, where models suggest that ice shelf melting is controlled by variable transport of Circumpolar Deep Water onto the continental shelf.